Peningkatan Motivasi Belajar melalui Strategi Ice Breaking pada Anak Usia 4-5 Tahun di PAUD Baitul Ilmi Sadar Sriwijaya: Increasiation Learning Motivation through the Ice Breaking Strategy in Children Aged 4-5 Years at PAUD Baitul Ilmi Sadar Sriwijaya - Sawitri, Ari; Susanti, Septiani Selly (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Every child is unique and diverse in the way they learn and interact. A teacher needs to understand these differences and be able to adapt Ice Breaking activities according to students' needs and interests. This research aims to see students' concentration and learning motivation by using Ice Breaking. The research method used is Classroom Action Research (PTK), the research data collection instruments are observation and interview techniques. The subjects of this research were children aged 4-5 years in Class B at PAUD Baitul Ilmi for the 2023/2024 academic year, totaling 20 students. The approach taken in this research is a descriptive approach. Based on the results of research on increasing children's learning motivation through the Ice Breaking technique, it is described as follows: The implementation of learning increased learning motivation through the Ice Breaking strategy in cycle I Meeting 2 10% was at the BSH point, in cycle II Meeting 2 it increased to 85%. The results of the research show that the solution that is considered appropriate is to include Ice Breaking in the process of teaching and learning activities, because students' concentration and learning motivation with Ice Breaking techniques in the learning process can increase.